Physical activity and life satisfaction: a study in Malaysian urban setting / Ahmad Hafizuddin Ahmad Shukri and Azman Ahmad Tajri - Ahmad Shukri, Ahmad Hafizuddin; Ahmad Tajri, Azman (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study investigates the relationship between physical activity and life satisfaction among Georgetown citizens [1]. By analyzing activity levels and satisfaction metrics, the research identifies demographic factors influencing well-being. Insights aim to inform interventions promoting exercise and enhancing happiness in urban settings, contributing to public health and policy development [2,3]. This study employed the International Physical Activity Questionnaire (IPAQ) and the Purpose in Life (PIL) test to measure physical activity and life satisfaction, respectively. Non-probability sampling targeted Georgetown citizens aged 20–60 years. Descriptive statistics summarized activity and satisfaction levels, while inferential tests, including correlation and t-tests, analyzed their relationship and gender differences.